Penerapan Media Pembelajaran Interaktif Berbasis Scratch dalam Meningkatkan Kemampuan Berhitung Siswa di Madrasah Ibtidaiyah - Diyah Andini Kusumastuti; M. Ali Ghufron (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Interest and motivation in learning mathematics among Madrasah Ibtidaiyah (MI) students remain relatively low, particularly in understanding basic arithmetic concepts such as addition and subtraction. This condition has led to poor learning outcomes and a lack of active student engagement in the learning process.This study aims to determine the effectiveness of Scratch-based learning media in improving MI students’ arithmetic skills. To achieve this objective, a qualitative research method with a case study approach was employed. Data were collected through observation, interviews, and documentation, and analyzed using the interactive analysis model of Miles and Huberman.The findings indicate that the use of Scratch media can enhance learning motivation, student engagement, and understanding of arithmetic concepts in a more enjoyable and interactive way. Thus, Scratch-based learning media is proven effective in improving the arithmetic skills of MI students. It is recommended that teachers utilize interactive digital media such as Scratch as an innovative alternative in teaching mathematics at the elementary madrasah level.